Cambridge global English learner's book stage 1 - Linse, Caroline; Schottman, Elly (New York : Cambridge, 2014)
The Learner's Book serves as the core instructional material for Stage 1, encompassing nine thematic units that integrate listening, speaking, reading, and writing activities. Each unit is structured around a central theme and includes six lessons, concluding with a project and self-assessment opportunity. The content is rich in illustrations and features various text types, including factual and fictional narratives, dialogues, and poetry. Key features such as 'Writing Tip', 'Language Detective', and 'Words to Remember' are incorporated to enhance vocabulary development and language awareness.
Keywords: Language Learning -- Learner's Book -- Cambridge Curriculum